(untitled) (Impetus, 2024)
The objective of this research was to determine the didactic support material that promotes the learning of technical gestures of freestyle swimming in the sports initiation process of 8-year-old children in the Inder Guarne children’s category during the second semester of the year. 2023. The methodology was qualitative with a descriptive scope and the interview and focus group were used as information collection techniques. The results showed that the use of pedagogical support materials in the process of sports initiation in swimming for learning freestyle encourages the development of recreational activities and the adaptation of material, encourages safety, confidence and interaction in the aquatic environment by of children, and contributes to the development of their dynamic posture, segmented coordination and general coordination. It is concluded that the teaching support materials most used by Inder Guarne teachers are the board, the kite, the ball and the Pull Boy and their use depends on the intention of the class session and the level of sports development of each one. of the kids.